PERAN MODERASI HEDGING TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN BADAN USAHA MILIK NEGARA (BUMN) : THE ROLE OF HEDGING MODERATION ON FINANCIAL DISTRESS IN STATE-OWNED ENTERPRISES - Herawati, Yesi; Dewi, Nurrahma (Universitas Riau, 2024)
Financial distress is one of the early signs of bankruptcy. A company that experiences financial distress continuously will have difficulty meeting its financial obligations. If this continues, it will lead to the bankruptcy of the company. This study aims to determine the condition of financial distress in State-Owned Enterprises in the non-banking sector listed on the Indonesia Stock Exchange in 2018-2022. The independent variables are growth opportunity and leverage, the dependent variable is financial distress, while the moderation variable is hedging. Population in State-Owned Enterprises in the non-banking sector. The sample used is nonprobability sampling with a saturated sampling technique. The data analysis method uses Partial Least Square (PLS). The results of this study show that growth opportunities and leverage have an impact on financial distress. Morover, hedging had strengtnes the relation between growth opportunities, leverage and financial distress. Furthermore, this research is expected to be able to add insight and encourage companies to make policies and decisions that are right and careful in running their companies so that the company does not experience bankruptcy.